Early Postoperative Arrhythmias after Paediatric Cardiac Surgery (Delta Medical College Journal, 2018)
Background: The radical change in techniques in paediatric cardiac surgery has dramatically reduced the morbidity and mortality. The different varieties of arrhythmia that are frequently observed in postoperative period in our country are still not well documented.Objectives: To determine the incidence and risk factors of arrhythmia immediately after cardiac surgery in paediatric age group.Materials and method: It was a prospective study. A total of 100 paediatric patients (age